Tooth development in a model reptile: functional and null generation teeth in the gecko Paroedura picta - Zahradnicek, Oldrich; Horacek, Ivan; Tucker, Abigail S (Journal of anatomy, 2012)
This paper describes tooth development in a basal squamate, Paroedura picta. Due to its reproductive strategy, mode of development and position within the reptiles, this gecko represents an excellent model organism for the study of reptile development. Here we document the dental pattern and development of non-functional (null generation) and functional generations of teeth during embryonic development. Tooth development is followed from initiation to cytodifferentiation and ankylosis, as the tooth germs develop from bud, through cap to bell stages. The fate of the single generation of non-functional (null generation) teeth is shown to be variable, with some teeth being expelled from the oral cavity, while others are incorporated into the functional bone and teeth, or are absorbed. Fate appears to depend on the initiation site within the oral cavity, with the first null generation teeth forming before formation of the dental lamina. We show evidence for a stratum intermedium layer in the enamel epithelium of functional teeth and show that the bicuspid shape of the teeth is created by asymmetrical deposition of enamel, and not by folding of the inner dental epithelium as observed in mammals.
Keywords: Tooth; Models, Animal; Lizards; modely u zvířat; odontogeneze; buněčná diferenciace; ještěři; Dental Enamel; Animals; zuby; zubní sklovina; Odontogenesis; zvířata; Cell Differentiation